Toward a Listening Bank: A review of best practices and the efficacy o f Beneficiary Assessment - Salmen, Lawrence (1998)
"This paper will first provide a descriptive overview of the beneficia ry assessment (BA) work done on World Bank projects (by region, sector , phase of cycle, and so forth); it will then discuss impact, both qua litatively (with case studies) and quantitatively; and finally it will propose a course that, if taken, could lead to a Bank that truly list ens and is attuned as much to the perspectives of the governments and peoples it serves as to the financial markets it helps sustain." "BAs use the qualitative techniques of conversational interviewing, focus g roups, and participant observation with representative samples of key actors, such as the intended—usually poor—beneficiaries, service provi ders, non-governmental organizations (NGOs) and other local public- an d private-sector leaders; analysis and the presentation of results are done as quantitatively as possible." Contents Beneficiary Assessment and the World Bank: An Overview Beneficiary Assessments in Africa Impa ct Case Studies Impact on Project Design Impact on Direct Cost Savings Summary of Quantifiable Impacts on Project Design and Objectives A No te on Methodology Complete the Paradigm Shift